Preventing Venous Thromboembolism in Ambulatory Cancer Patients: The ONKOTEV Study. (19th April 2017) - Cella, Chiara Alessandra; Di Minno, Giovanni; Carlomagno, Chiara; Arcopinto, Michele; Cerbone, Anna Maria; Matano, Elide; Tufano, Antonella; Lordick, Florian; De Simone, Biagio; Muehlberg, Katja Sibylle; Bruzzese, Dario; Attademo, Laura; et al.
Abstract : Background: The efficacy of risk model scores to predict venous thromboembolism (VTE) in ambulatory cancer patients is under investigation, aiming to stratify on an individual risk basis the subset of the cancer population that could mostly benefit from primary thromboprophylaxis. Materials and Methods: We prospectively assessed 843 patients with active cancers, collecting clinical and laboratory data. We screened all the patients with a duplex ultrasound (B‐mode imaging and Doppler waveform analysis) of the upper and lower limbs to evaluate the right incidence of VTE (both asymptomatic and symptomatic). The efficacy of the existing Khorana risk model in preventing VTE was also explored in our population. Several risk factors associated with VTE were analyzed, leading to the construction of a risk model. The Fine and Gray model was used to account for death as a competing risk in the derivation of the new model. Results: The risk factors significantly associated with VTE at univariate analysis and further confirmed in the multivariate analysis, after bootstrap validation, were the presence of metastatic disease, the compression of vascular/lymphatic structures by tumor, a history of previous VTE, and a Khorana score >2. Time‐dependent receiving operating characteristic (ROC) curve analysis showed a significant improvement in the area under the curve of the new score over the Khorana model at 3 months (71.9% vs. 57.9%, p = .001), 6 months (75.4% vs. 58.6%, p < .001), and 12 months (69.8% vs. 58.3%, p = .014). Conclusion: ONKOTEV score steps into history of cancer‐related‐VTE as a promising tool to drive the decision about primary prophylaxis in cancer outpatients. The validation represents the goal of the prospective ONKOTEV‐2 study, endorsed and approved by the European Organization for Research and Treatment of Cancer Young Investigators Program. Abstract : Stratification of risk through predictive models is a strategic method for reducing the burden of venous thromboembolism in cancer patients. The objective of this study was to derivate a novel predictive scoring tool for measuring the risk of the individual patient.